Impact of Diabetic Status on Outcomes After Revascularization With Drug-Eluting Stents in Relation to Coronary Artery Disease Complexity: Patient-Level Pooled Analysis of 6081 Patients. (February 2016) - Koskinas, Konstantinos C.; Siontis, George C.M.; Piccolo, Raffaele; Franzone, Anna; Haynes, Alan; Rat-Wirtzler, Julie; Silber, Sigmund; Serruys, Patrick W.; Pilgrim, Thomas; Räber, Lorenz; Heg, Dik; Jüni, Peter; et al.
Abstract : Background—: Diabetes mellitus and angiographic coronary artery disease complexity are intertwined and unfavorably affect prognosis after percutaneous coronary interventions, but their relative impact on long-term outcomes after percutaneous coronary intervention with drug-eluting stents remains controversial. This study determined drug-eluting stents outcomes in relation to diabetic status and coronary artery disease complexity as assessed by the Synergy Between PCI With Taxus and Cardiac Surgery (SYNTAX) score. Methods and Results—: In a patient-level pooled analysis from 4 all-comers trials, 6081 patients were stratified according to diabetic status and according to the median SYNTAX score ⩽11 or >11. The primary end point was major adverse cardiac events, a composite of cardiac death, myocardial infarction, and clinically indicated target lesion revascularization within 2 years. Diabetes mellitus was present in 1310 patients (22%), and new-generation drug-eluting stents were used in 4554 patients (75%). Major adverse cardiac events occurred in 173 diabetics (14.5%) and 436 nondiabetic patients (9.9%; P <0.001). In adjusted Cox regression analyses, SYNTAX score and diabetes mellitus were both associated with the primary end point ( P <0.001 and P =0.028, respectively; P for interaction, 0.07). In multivariable analyses, diabetic versus nondiabetic patients had higher risks of major adverse cardiac events (hazard ratio, 1.25; 95% confidence interval, 1.03–1.53; P =0.026) and target lesion revascularization (hazard ratio, 1.54; 95% confidence interval, 1.18–2.01; P =0.002) but similar risks of cardiac death (hazard ratio, 1.41; 95% confidence interval, 0.96–2.07; P =0.08) and myocardial infarction (hazard ratio, 0.89; 95% confidence interval, 0.64–1.22; P =0.45), without significant interaction with SYNTAX score ⩽11 or >11 for any of the end points. Conclusions—: In this population treated with predominantly new-generation drug-eluting stents, diabetic patients were at increased risk for repeat target-lesion revascularization consistently across the spectrum of disease complexity. The SYNTAX score was an independent predictor of 2-year outcomes but did not modify the respective effect of diabetes mellitus. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifiers: NCT00297661, NCT00389220, NCT00617084, and NCT01443104. Abstract : Supplemental Digital Content is available in the text.